Maintenance antipsychotic medication patterns in outpatient schizophrenia patients: a naturalistic cohort study. - Burns, T; Christova, L; Cooper, S; Harrison, G; McKendrick, J; Laugharne, R; Obuaya, T; McCreadie, R; O'Brien, S; Perrington, S; Stephenson, D (2006)
OBJECTIVE: Newer antipsychotics are increasingly used in schizophrenia maintenance. The UK change has been slow with little known on switching patterns. We aimed to investigate antipsychotic prescribing patterns in schizophrenia patients. METHOD: A naturalistic six-site cohort sample of 600 patients were interviewed by researchers at 6-monthly intervals for 2 years to record their clinical and social functioning; use of services and medication for the preceding 6 months was obtained by structured extraction from clinical case notes. RESULTS: Alterations in antipsychotic medication were frequent in this group, mainly during periods of inpatient care. Atypical prescribing increased steadily, though slowly, across the period. Polypharmacy was less than anticipated. CONCLUSION: Inpatient care remains the main forum for switching of antipsychotics. The UK maintains a slow shift to atypical antipsychotics.